2004
DOI: 10.1124/mol.104.004846
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation and Relocalization of the Platelet P2Y Receptors after Activation: A Way to Avoid Loss of Hemostatic Properties?

Abstract: In the present study, we investigated the desensitization and trafficking of the P2Y 1 and P2Y 12 receptors after agonist-induced stimulation of platelets or astrocytoma cells transfected with the P2Y 1 or P2Y 12 receptors fused to green fluorescent protein. In platelets and in transfected cells, exposure to 10 M ADP caused desensitization of the P2Y 1 receptor-driven calcium signal, whereas the P2Y 12 receptor-mediated inhibition of cAMP formation was not affected. Plasma membranes from ADP-stimulated platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 36 publications
3
74
2
Order By: Relevance
“…As with other GPCRs, the responsiveness of P2Y 1 and P2Y 12 receptors is tightly regulated. Recently, we showed that both P2Y 1 and P2Y 12 receptor responses desensitize in human platelets [4], in agreement with the observed desensitization of platelet responses following prolonged exposure to ADP [5][6][7]. Mechanisms underlying desensitization are complex and can involve phosphorylation of the receptor, uncoupling from G proteins, internalization, and ultimately intracellular downregulation [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 54%
“…As with other GPCRs, the responsiveness of P2Y 1 and P2Y 12 receptors is tightly regulated. Recently, we showed that both P2Y 1 and P2Y 12 receptor responses desensitize in human platelets [4], in agreement with the observed desensitization of platelet responses following prolonged exposure to ADP [5][6][7]. Mechanisms underlying desensitization are complex and can involve phosphorylation of the receptor, uncoupling from G proteins, internalization, and ultimately intracellular downregulation [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 54%
“…Both receptors (P2Y 1 and P2Y 12 ) are internalized, however, with different kinetics and through different pathways. This resulted in a greater persistence of the P2Y 12 receptor at the plasma membrane in the presence of nucleotide in the medium, while the P2Y 1 receptor remained internalized [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of this phenomenon have been studied in detail, but consensus has not been reached, and two different views have not yet been reconciled. On the one hand, it is thought that the phenomenon of platelet refractoriness to ADP is due to selective desensitization and internalization of the P2Y 1 receptor, while the P2Y 12 receptor remains functional with the ability of ADP to induce amplification of the platelet aggregation induced by other agonists [89][90][91]. Desensitization of the P2Y 1 receptor has been shown to be dependent on receptor C-terminal phosphorylation sites, β-arrestin-2 interaction and protein kinase C (PKC) activity [92,93].…”
Section: Desensitizationmentioning
confidence: 99%